Affecters on Housing Prices: An Initial Review in Malaysia - Senawi, Azhan Rashid; Hisham, Azra Irdina Zul; Azizi, Nur Syakirah; Anuar, Nor Iffah Masturah Shamsul; Harun, Shariff (Information Management and Business Review, 2024)
This research delves into the intricate dynamics of the Malaysian housing market. Due to the issue of constantly high and expensive house prices, the study aims to integrate the possible macroeconomic causes as well as the integrity issue by focusing on three vital independent variables: Gross Domestic Product (GDP), Foreign Direct Investment (FDI), and Corruption Index (CRP). The research uses quantitative methods, the Ordinary Least Squares (OLS), to reveal nuanced correlations between these economic variables and house prices in Malaysia. The intriguing findings show that both FDI and CRP significantly influence house prices positively, aligning with existing literature. However, the unexpectedly insignificant correlation between GDP and house prices suggests a potential gap in understanding, adding a layer of intrigue to the research. These results and significant findings offer valuable insights for decision-makers and emphasize the importance of ongoing research to better grasp the complex factors shaping housing markets in different economic situations.